Residue behaviors and dietary risk of cyazofamid in turnip, onion and romaine lettuce assessed by a QuEChERS-LC-MS/MS method - Ruijuan Li; Xue Men; Rumei Li; Tongjin Liu; Hui Liang; Feng Fang; Dongxiao Sun-Waterhouse; Yongli Wang (Food Science and Human Wellness)
In this study, the dissipation, terminal residues and dietary risk of the cyazofamid residue in three globally consumed minor crops, turnip (Brassica rapa L.), onion (Allium cepa L.) and romaine lettuce (Lactuca sativa L.) were assessed by supervised field trials at 6 locations of China in 2020. A reliable QuEChERS-LC-MS/MS method was developed for simultaneous analysis of cyazofamid and its primary metabolite, 4-chloro-5-p-tolylimidazole-2-carbonitrile (CCIM). The average recoveries of cyazofamid and CCIM in turnip, onion and romaine lettuce were 79 %–97 % and 77 %–99 %, respectively. The half-lives of cyazofamid in these crops were 5.7–6.5, 5.3–8.7 and 5.8–6.5 days in turnip, onion and romaine lettuce, respectively, with the final cyazofamid residues at harvest all lower than limit of quantitation (LOQ, 0.01 mg/kg). The turnip roots, onion bulbs and romaine lettuce leaves grown in China under Good Agricultural Practices conditions and harvested 10, 14 and 5 days, respectively, after the cyazofamid SC (100 g/L) application, would be reasonably safe for consumption by the general population. The maximum residue limit (MRL) values of cyazofamid could be tentatively set as 10 mg/kg for turnip leaves, 0.3 mg/kg for turnip roots, 0.05 mg/kg for onion bulbs, and 10 mg/kg for romaine lettuce leaves.